Financial cycle: A critical analysis of the methodology for its identification - Łukasz Kurowski (Journal of Central Banking Theory and Practice, 2021)
While the legitimacy of the concept of the financial cycle (as distinct from the business cycle) in research and economic policy after the experience of the global financial crisis raises no concerns, the methodology for its application has become a subject of discussion. The purpose of this article is to indicate which research methods dominate in identifying a financial cycle and which methodological traps accompany them. The low level of critical perspective on the methods used to identify cycles often results in conclusions that have no economic justification and may result in erroneous decisions in economic policy and central bank practice. The case study carried out in the article confirms that the key elements in identifying a financial cycle are part of a long-term series covering at least two lengths of the financial cycle. In addition, because the results may be sensitive to the type of filter used, it is important not to rely on a single variable but rather to build indexes that take into account a number of them (including those obtained using filtration methods).
Keywords: C22; E32; E61; G01; 330; financial cycle; macroprudential policy; financial stability; filtration methods